(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A total of 206 ducks were subjected to routine postmortem examinations from July 2007 to June 2008. Of the ducks examined, 167 (81.1 %) were infected by one/more species of gastro-intestinal helminths. A total of ten species of helminth parasites were recovered from gastrointestinal tract, of which four species were trematodes namely: Echinostoma revolutum, Notocotylus attenuatus, Hypoderaeum conoideum and Echinoparyphium recurvatum; two were nematodes, namely, Amidostomum anseris, Capillaria contorta; two were cestodes, viz, Hymenolepis coronula and Fimbriaria fasciolaris and two species belonged to acanthocephala such as, Arythmorhynchus anser and Filicollis anatis. Single double and mixed infections were found in 78 (46.7%), 46 (27.5%) and 43 (25.8%) ducks, respectively. Prevalence of gastrointestinal helminth was significantly (P<0.05) higher in female ducks (82.7 %) than male ducks (77.6%). Ducks above six month to one year of age were more affected (53.9%) than the ducks < 6 month (15.0%) and > 1 year of age (31.1%). Helminth infection was significantly (P<0.05) lower in rainy season (64.9%) in contrast to summer (75.7 %) and winter season (91.1 %). In heavy infections of E. revolutum haemorrhagic enteritis were noticed and parasites were firmly attached with the mucosa. E. recurvatum caused thickening of the serosal surface of intestinal wall. N. attenuatus produced catarrhal tryplitis characterized by thickening of the villi and formation of oeosinophilic granulomas. Massive infections with H. coronula produced inflammatory changes in the small intestine. Grossly petechial haemorrhages to ulcerative lesions were produced by A. anseris. In proventriculus circular ulcerative and necrotic areas with degeneration of the glandular tissues were seen. A. anser was also found in between the horney and muscular layer of the gizzard where they produced pin pointed haemorrhagic lesions and in severe case parasites were embedded into the mucosal layers of gizzard. For the control of helminths infections mass deworming is necessary. Keywords: Gastro-intestinal helminths; Ducks; Epidemiology; Pathology DOI: 10.3329/jbau.v7i1.4969 J. Bangladesh Agril. Univ. 7(1): 91-97, 2009